Pengaruh Tari Panen Modifikasi Terhadap Perkembangan Motorik Kasar Anak Usia 5-6 Tahun Di Taman Kanak-kanak Ramah Anak Nagari Gurun Panjang Kabupaten Pesisir Selatan - Putri Yanti, Dini; Anggraini, Vivi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
This research is motivated by the lack of gross motor development in children, some children who have not been able to carry out several activities that blend with physical gross motor skills. The aim of this study was to determine the effect of the modified harvest dance on the gross motor development of children aged 5-6 years at the Nagari Gurun Panjang Child Friendly Kindergarten. Learning to develop children's gross motor skills needs to pay attention to the dance used. The use of modified harvest dance has never been carried out by teachers to develop children's gross motor development. This study uses a quantitative approach using experimental methods. Tried the research instrument by validating it and the results can be seen through SPSS 26 which shows that the Sig. (2-tailed) of 0.041 <0.05 which indicates that there are differences in Pre-Test and Post-Test scores obtained by children or it can be said that modified harvest dance activities can significantly influence gross motor development of children aged 5-6 years in Kindergarten Child Friendly Nagari Desert Panjang